2015
DOI: 10.1371/journal.pone.0132889
|View full text |Cite
|
Sign up to set email alerts
|

Superiority of Minimally Invasive Oesophagectomy in Reducing In-Hospital Mortality of Patients with Resectable Oesophageal Cancer: A Meta-Analysis

Abstract: BackgroundCompared with open oesophagectomy (OE), minimally invasive oesophagectomy (MIO) proves to have benefits in reducing the risk of pulmonary complications for patients with resectable oesophageal cancer. However, it is unknown whether MIO has superiority in reducing the occurrence of in-hospital mortality (IHM).ObjectiveThe objective of this meta-analysis was to explore the effect of MIO vs. OE on the occurrence of in-hospital mortality (IHM).Data SourcesSources such as Medline (through December 31, 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(64 citation statements)
references
References 102 publications
2
60
0
2
Order By: Relevance
“…The colon can be observed entering the hernia (1). After the colon is reduced, the left lobe of the liver is mobilized to free the diaphragm anteriorly (2). The view after reduction shows the gastric conduit and the aorta (3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The colon can be observed entering the hernia (1). After the colon is reduced, the left lobe of the liver is mobilized to free the diaphragm anteriorly (2). The view after reduction shows the gastric conduit and the aorta (3).…”
Section: Resultsmentioning
confidence: 99%
“…Advantages of minimal access approaches to the esophagus include a lower risk of postoperative chest infection, shorter length of stay, quicker return to work and post-operative recovery [2][3][4]. There are cited disadvantages, including higher rates of gastric conduit necrosis and anastomotic leak [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Zhou et al [24] reported significant decrease in the morbidity of arrhythmia and pulmonary embolism in MIO group. Corresponding to this, (see Table 3), we found MIO to be superior to OE in reducing morbidity of system complications, according to the pooled OR = 0.777.…”
Section: Discussionmentioning
confidence: 99%
“…So far, only four randomized studies have done their jobs and that is the reason why the majority of the existed meta-analyses were based on retrospective studies. Among those meta-analyses that had been done before us: Sgourakis et al8 compared postoperative outcomes and survival between MIE and OE and revealed that both groups have the same in-hospital results and prognosis; Nagpal et al9 analyzed postoperative outcomes, including the 30-day mortality and anastomotic leakage of MIE and OE and revealed that there was no significant difference in the mortality; Zhou et al10,11 compared anastomotic leakage and in-hospital mortality between the two groups, and the outcome showed that MIE has superiority over OE as the former could reduce the in-hospital mortality rate; however, there was no evidence that MIE could decrease the anastomotic leakage; and Guo et al12 indicated that MIE can achieve significant long-term survival rates and reduce perioperative complications.…”
Section: Discussionmentioning
confidence: 99%